Calculation of the polarization of light emitted during electron-impact excitation of Ba+ - Bostock, Christopher; Fursa, Dmitry; Bray, Igor (American Physical Society, 2014)
The measurements of Crandall et al. [Phys. Rev. A 10, 141 (1974)] for the polarization of light emitted during electron-impact excitation of Ba+ are in significant disagreement with relativistic distorted wave scattering theory calculations of Sharma et al. [Phys. Rev. A 83, 062701 (2011)]. The relativistic convergent close-coupling (RCCC) method is applied to the problem and the discrepancy between theory and experiment is resolved across the full range of energies measured. Furthermore, the oscillations in the polarization fraction measurements at low energies near threshold are reproduced by the RCCC calculations and linked to the formation of autoionizing states of neutral Ba.